Maternal Vitamin D, Oxidative Stress, and Preeclampsia. Issue 2 (24th June 2022) - Wei, S.Q.; Bilodeau, J.-F.; Julien, P.; Luo, Z.-C.; Abenhaim, H.A.; Bi, W.G.; Nuyt, A.M.; Leduc, L.; Audibert, F.; Fraser, W.D.
Abstract : ( Int J Gynecol Obstet . 2021;154:444–450) Preeclampsia (PE) is a serious and complex pregnancy-related disorder with negative effects on both the mother and fetus. Prevention is vital to reduce 18% of maternal mortality that results from PE in the United States each year. After years of study, its causes and mechanisms have not yet been fully unraveled. A recent review and analysis have shown an association between maternal vitamin D levels during pregnancy and an increased risk of PE.